Tinjauan Hukum Atas Pembatalan Risalah Lelang Karena Adanya Kepentingan Yang Dirugikan Akibat Dari Keputusan Tata Usaha Negara (Studi Kasus Putusan Mahkamah Agung Nomor 486 K/TUN/2017) - Enrawati Enrawati (Fakultas Hukum universitas Islam Sumatera Utara, 2020)
AbstractAuction is the most beneficial means of entering into an agreement or agreement for the seller by gathering interested people. The main requirement is to gather interested people to enter into a sale and purchase agreement that is most profitable for the seller.The problems in this study are: legal arrangements for the determination of auction minutes that apply in accordance with the provisions of the law, forms of cancellation of state administrative decisions that can harm the interests of other parties, judges' consideration in the validity of canceling auction minutes in the decision of the Supreme Court Number 486 K / TUN / 2017.This research is descriptive with a normative juridical approach.